Sphaerolejeunea (Lejeuneaceae, Porellales) is a synonym of Lejeunea - Heinrichs, Jochen; Dong, Shanshan; Feldberg, Kathrin; Schäfer-Verwimp, Alfons; Schmidt, Alexander R. (Phytotaxa, 2012)
Phylogenetic analyses of a three marker dataset of Lejeuneaceae (chloroplast genome rbcL gene and trnL-F region, and nuclear ribosomal ITS1-5.8S-ITS-2 region) show the presence of the monospecific genus Sphaerolejeunea in a robust subclade of Lejeunea. We treat Sphaerolejeunea as a synonym of Lejeunea, and propose a new name for Sphaerolejeunea umbilicata, Lejeunea drehwaldii.